Research on Reclaimed Water Utilization Strategies in Shenzhen - ZHANG Xiaoju (Renmin Zhujiang)
Water shortage has become an important bottleneck issue,which restricts the rapid development of cities.The efficient utilization of reclaimed water becomes one of the most important ways to implement the scientific concept of circular economy,energy conservation,and emission reduction,and it is an important measure to solve the shortage of water resources and ensure urban development. Based on the complex comprehensive utilization of reclaimed water in Shenzhen,this paper used several different measures to improve the utilization rate,including optimizing the spatial layout,sorting out key regions,improving the system,and refining the management mechanism.In addition,Guangming District was selected as a pilot and explored.Different strategies were adopted for different types of reclaimed water users to maximize social,economic,and environmental benefits.Through research on the efficient utilization approaches of reclaimed water in Shenzhen,the paper provides strong support and guarantee for solving the shortage of urban water resources and promotes the sustainable and high-quality development of cities.